Implementation of the Discovery Learning Strategy in Islamic Cultural History Education - Sofia Nisa Ulyantika; Hidayat; Fitri Istiqomah (Bulletin of Pedagogical Research, 2023)
This study aims to explore the implementation of the Discovery Learning strategy in teaching Islamic Cultural History to tenth-grade social science students at MAM Lakitan. The research method used is descriptive qualitative with data collected through observation, interviews, and documentation. The primary data sources are religious education teachers who have applied the Discovery Learning strategy, while the secondary sources include the school principal and administrative staff. The results show that while teachers attempt to apply Discovery Learning in the classroom, several challenges arise, including low student motivation, lack of interest in Islamic Cultural History, limited use of instructional media, and poor student discipline. Despite these issues, teachers make efforts to motivate students and diversify the use of teaching media. The study concludes that although the Discovery Learning strategy holds potential to improve student engagement and understanding, its effectiveness depends greatly on student readiness, teacher creativity, and institutional support.